Big five personality traits and coping styles predict subjective well-being: A study with a Turkish Sample - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
The purpose of the study is to examine the relationships among big five personality traits, coping styles and subjective wellbeing in a selected Turkish sample that consisted of 251 undergraduate students obtained from Psychological Counseling and Guidance Department at Marmara University. Data were collected using Subjective Well-being Scale (Tuzgol Dost, 2005), Coping Styles Scale (Hisli Sahin and Durak, 1995) and Big Five Personality Inventory Short Form- NEO-FFI (Gulgoz, 2002). To analyze the data, a hierarchical regression analysis was conducted to determine the relationships with personality traits, coping styles and subjective well-being. The results revealed that neuroticism was a negative predictor of subjective well-being whereas extraversion and conscientiousness were positive predictors of subjective well-being. In addition to this, self-confident coping style was found to predict subjective well-being positively while helpless coping style predicted subjective well-being negatively. These results suggest that personality traits and coping styles play significant role in explaining subjective well-being. (C) 2009 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Dr. Zafer Bekirogullari of Y.B.
Keywords: Subjective well-being; big five; coping styles; personality traits; undergraduate students